Mathematical problem-solving ability: The impact of self-regulated learning on the system of linear inequalities in two variables - Amalia, Hilda; Jusra, Hella (Desimal: Jurnal Matematika, 2022)
This research aims to analyze the mathematical problem-solving ability of students in terms of self-regulated learning. The method used in this research is the qualitative descriptive method. There are 4 indicators of problem-solving ability in this research, namely understanding the problem, formulating the problem, solving the problem, and re-examining the answers. The four indicators of problem-solving ability can be met by subjects who have a high self-regulated learning category. Subjects with medium self-regulated learning category were only able to fulfill 3 indicators of problem-solving ability. Meanwhile, subjects with low self-regulated learning were only able to fulfill 2 indicators of problem-solving ability. The results showed that the ability to solve problems with high categories was owned by subjects with high self-regulated learning.